Measurement report: Changing characteristics of atmospheric CH4 in the Tibetan Plateau: records from 1994 to 2019 at the Mount Waliguan station - S. Liu; S. Liu; S. Liu; S. Fang; P. Liu; M. Liang; M. Guo; Z. Feng; Z. Feng (Atmospheric Chemistry and Physics, 2021)
A 26-year, long-term record of atmospheric methane (CH4) measured in situ at the Mount Waliguan (WLG) station, the only World Meteorological Organization (WMO) and Global Atmosphere Watch (GAW) global station in inland Eurasia, is presented. Overall, a nearly continuous increase in atmospheric CH4 was observed at WLG, with a yearly growth rate of 5.1±0.1 parts per billion (ppb) per year during 1994–2019, except for some particular periods with near-zero or negative values, e.g., 1999–2000 and 2004–2006. The average CH4 mole fraction was only 1799.0±0.4 ppb in 1994 but increased to about 133 ppb and reached a historic level of 1932.0±0.1 ppb in 2019. The case study in the Tibetan Plateau showed that the atmospheric CH4 increased rapidly. During some special periods, it is even larger than that of city regions (e.g., 6.7±0.2 ppb yr−1 in 2003–2007). Generally, the characteristics of CH4 varied in different observing periods as follows: (i) the diurnal cycle has become apparent and the amplitudes of the diurnal or seasonal cycles increased over time; (ii) the wind sectors with elevated CH4 mole fractions switched from ENE-E-ESE-SE-SSE sectors (wind directions) in early periods to NNE-NE-ENE-E sectors in later years; (iii) the area of source regions increased as the years progressed, and strong sources shifted from northeast (city regions) to southwest (northern India); and (iv) the annual growth rates in recent years (e.g., 2008–2019) were significantly larger than those in the early periods (e.g., 1994–2007).